The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s2176-94512012000400024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid maxillary expansion on the dimension of the nasal cavity and on facial morphology assessed by acoustic rhinometry and rhinomanometry

Abstract: OBJECTIVE: To assess the effects of rapid maxillary expansion on facial morphology and on nasal cavity dimensions of mouth breathing children by acoustic rhinometry and computed rhinomanometry. METHODS: Cohort; 29 mouth breathing children with posterior crossbite were evaluated. Orthodontic and otorhinolaryngologic documentation were performed at three different times, i.e., before expansion, immediately after and 90 days following expansion. RESULTS: The expansion was accompanied by an increase of the maxilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 14 publications
(10 reference statements)
0
21
0
Order By: Relevance
“…14 On the other hand, Langer et al 34 concluded that RME did not influence nasal resistance in their long-term evaluation. Itikawa et al 35 and Matsumoto et al 36 examined the effects of RME on nasal cavity dimensions of young children and observed a significant increase in nasal transverse bony width. However, no difference in nasal volume was detected as a result of mucosal compensation.…”
Section: Discussionmentioning
confidence: 99%
“…14 On the other hand, Langer et al 34 concluded that RME did not influence nasal resistance in their long-term evaluation. Itikawa et al 35 and Matsumoto et al 36 examined the effects of RME on nasal cavity dimensions of young children and observed a significant increase in nasal transverse bony width. However, no difference in nasal volume was detected as a result of mucosal compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 presents recent longitudinal studies on the effect of maxillary expansion on nasal respiration. [63][64][65][66][67][68] While some studies have shown that RME improves nasal cavity dimensions and reduces nasal resistance, 63,[67][68][69] they generally have a short-term follow-up (≤1 year), a small sample size and lack of a control group. 70,71 An early highly-cited study by Hershey et al reported that RME reduced nasal resistance by 45% in 17 children aged between 11 and 14 years over a 3-month period.…”
Section: Does Nasorespiratory Obstruction Alter Dentofacial Growth?mentioning
confidence: 99%
“…Most studies have relatively sample sizes that carry a low statistical power and raise questions about data representativeness (of the overall population). 17,20,37,49,52,53,[63][64][65][66][67][68][69] The lack of an adequate control makes it difficult to measure the effect of any intervention against normal growth. 28,[64][65][66][67]69 Even studies with control groups frequently lack a properly-matched cohort, such as untreated patients with large adenoids when investigating adenotonsillectomy.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…As for surgical approaches, research has demonstrated the benefits of adenotonsillectomy for 18 children with adenotonsillar hypertrophy in order to allow the return of nasal breathing, benefit to the dental occlusion, favoring the adequate morphofunctional development of the face 44 . Another article analyzed the effect of rapid maxillary expansion surgery in 29 children and it was found that this procedure, by itself, is not justified to induce a nasal breathing pattern in oral breathers 45 .…”
Section: Treatmentsmentioning
confidence: 99%